Evaluating User Interface Design Of Skype And Google Talk Based On Android Platform - Arnold Nasir (TEMATIKA: Jurnal Penelitian Teknik Informatika dan Sistem Informasi, 2015)
As technology advances, more and more applications are developed with the intent of making our lives easier. Communication is an important part of our everyday lives; so many technologies have been developed for this purpose. Voice over Internet Protocol (VoIP) is a technology that is used for making both textual and vocal communication. VoIP applications are gaining popularity due to the low cost and high quality service, which is comparable to the traditional telephone service. Nowadays, Skype, which is owned by Microsoft, is the most popular VoIP service with 405 million registered users and 15 million active online users. Google Talk, owned by Google is also a popular VoIP application. This study compared the interface and usability of both these applications and found that Skype was by far the most user friendly and attractive.